Associations of audiometric hearing and speech-in-noise performance with cognitive decline among older adults: The Baltimore Longitudinal Study of Aging (BLSA) - Jiang, Kening; Armstrong, Nicole M.; Agrawal, Yuri; Gross, Alden L.; Schrack, Jennifer A.; Lin, Frank R.; Ferrucci, Luigi; Resnick, Susan M.; Deal, Jennifer A.; Powell, Danielle S. (Frontiers in Neurology, 2022)
Background: Established associations between hearing loss and cognitive decline were primarily defined by pure-tone audiometry, which reflects peripheral hearing ability. Speech-in-noise performance, which reflects central hearing ability, is more limited in prior literature. We examined the longitudinal associations of audiometric hearing and speech-in-noise performance with cognitive decline. Methods: We studied 702 participants aged ≥60 years in the Baltimore Longitudinal Study of Aging 2012-2019. Global and domain-specific (language, memory, attention, executive function, visuospatial ability) cognitive performance were assessed by the cognitive assessment battery. Hearing thresholds at 0.5, 1, 2 and 4 kilohertz obtained from pure-tone audiometry were averaged to calculate better-ear pure-tone average (PTA) and participants were categorized as having hearing loss (>25 decibels hearing level [dB HL]) or normal hearing (≤25 dB HL). Speech-in-noise performance was assessed by the Quick Speech-in-Noise (QuickSIN) test, and participants were categorized as having below-median (worse) or above-median performance. Linear mixed effects models with random intercepts and slopes were used to assess baseline cognitive performance and cognitive decline by hearing status. Models adjusted for demographic, lifestyle and disease factors. Results: Participants with audiometric hearing loss showed similar baseline cognitive performance but faster decline in global cognitive function, language, executive function, and attention. Participants with below-median QuickSIN score showed worse baseline cognitive performance in all domains and faster decline in global cognitive function, language, memory, executive function and attention. Conclusions: Audiometric hearing might be targeted to delay cognitive decline. Speech-in-noise performance might be a novel marker and might be more sensitive to memory decline.